A Theoretical Analysis of Aniline-Based Dyes Structure Modification to Improve the Efficiency of Dye-Sensitized Solar Cells (DSSCs) - Imelda Imelda; Hermansyah Aziz; Arxhel Septino Faril Nanda; Elvira Deswita (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
This study employed aniline-based D-π-A organic dyes, consisting of four dyes differentiated by their π-conjugated moieties. Calculations were performed using DFT/TD-DFT with the B3LYP/6-31G basis set. The work examined structural modifications of aniline-based D-π-A dyes in the gas phase to identify π-conjugated variations with high sensitizing potential for DSSCs. Among the dyes evaluated, Dye 2 (8-(4-aminophenyl)-9H-purine-2-carboxylic acid) showed the most promising characteristics, with an absorption maximum (λmax) of 504.45 nm and a bandgap of 3.0618 eV. These findings indicate that converting aniline dyes into D-π-A systems can improve DSSC performance.